2006
DOI: 10.1002/j.1551-8833.2006.tb07613.x
|View full text |Cite
|
Sign up to set email alerts
|

Filtration processes—A distinguished history and a promising future

Abstract: This article chronicles advances in the filtration of public drinking water supplies from the late 1800s to today and discusses the future of filtration. Topics covered include: granular media's evolution over the years; pretreatment practices consisting of coagulation, mixing and clarification; current availability of filters and membranes; and, future advances in filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Before the study, the filters had been operating continuously for 18 months. Backwashing consisted of a 2 min air scour (61 m s −1 ) followed by a dechlorinated water only wash (81 m s −1 ) for 5 min and sampling took place over 5 days. Filter influent and effluent were collected immediately prior to backwash, immediately after backwash and 2, 5 days post‐backwash.…”
Section: Biofilter Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the study, the filters had been operating continuously for 18 months. Backwashing consisted of a 2 min air scour (61 m s −1 ) followed by a dechlorinated water only wash (81 m s −1 ) for 5 min and sampling took place over 5 days. Filter influent and effluent were collected immediately prior to backwash, immediately after backwash and 2, 5 days post‐backwash.…”
Section: Biofilter Designmentioning
confidence: 99%
“…One of the first filtration systems installed for a centralized system was in Paisley, Scotland in 1804 which was used to treat water for both industrial purposes and to supply water to the local population; at the time cleaned water was delivered by cart to residents . In North America filtration was first implemented at Poughkeepsie, NY, USA in 1872 . Early filtration systems utilized slow sand filtration practices, which as the name may imply, have very low filtration rates (ranging from approximate initial historical lows of 0.1 m h −1 to more modern averages of 0.4 m h −1 ); rapid granular filtration has much higher filtration rates, ranging from approximately 5 to 20 m h −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously demonstrated that GAC filter can provide attachment sites for biofilm accumulation and thus additionally remove previously adsorbed organic matter (Kim et al 1997). The production of bacteria from such biological activated carbon filters is considered as a disadvantage of the treatment operation because potential pathogens may pose a serious health risk to the consumers (Logsdon et al 2006). …”
Section: Gac Filtrationmentioning
confidence: 99%
“…Rapid sand filters were later favoured over slow sand because of the large area required by the latter to maintain a sufficient output and the excessively low filtration rates (0.1-0.3 m/h, or lower), also due to the smaller size of the sand grains [8]. Recently, it has been successfully adopted in many small communities because of the efficacy in removing protozoa pathogens [8,30]. Slow sand filtration is not, however, effective when dealing with high levels of turbidity and algae because of a limited removal ability and long ripening times [5,31].…”
Section: Filtration Operating Setupmentioning
confidence: 99%